2023
DOI: 10.3390/ani13040722
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Variants Identified with Multiple Genome-Wide Association Study Methods Optimizes Genomic Selection for Growth Traits in Pigs

Abstract: Improving the prediction accuracies of economically important traits in genomic selection (GS) is a main objective for researchers and breeders in the livestock industry. This study aims at utilizing potentially functional SNPs and QTLs identified with various genome-wide association study (GWAS) models in GS of pig growth traits. We used three well-established GWAS methods, including the mixed linear model, Bayesian model and meta-analysis, as well as 60K SNP-chip and whole genome sequence (WGS) data from 173… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 95 publications
0
1
0
Order By: Relevance
“…Our results indicated that the use of preselected variants from a large GWAS meta-analysis has shown small and non-robust improvements in the accuracy of genomic prediction compared to using all variants from the SNP chip data in pigs. A previous study [22] based on preselected variants by p-value ranking from GWAS results demonstrated an improvement in the accuracy of genomic prediction for BFT, ADG, and loin muscle area across different pig breeds. The improvement ranged from 4 to 13.2% compared to the SNP chip data, which was slightly higher than our results.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our results indicated that the use of preselected variants from a large GWAS meta-analysis has shown small and non-robust improvements in the accuracy of genomic prediction compared to using all variants from the SNP chip data in pigs. A previous study [22] based on preselected variants by p-value ranking from GWAS results demonstrated an improvement in the accuracy of genomic prediction for BFT, ADG, and loin muscle area across different pig breeds. The improvement ranged from 4 to 13.2% compared to the SNP chip data, which was slightly higher than our results.…”
Section: Discussionmentioning
confidence: 98%
“…One of the most successful strategies to improve the accuracy of genomic predictions is the utilization of preselected variants associated with the trait of interest from WGS data. In recent years, preselected potential causal variants identified through genome-wide association studies (GWASs) have already been applied in genomic prediction to improve the prediction accuracy for a variety of traits in livestock and poultry [19,20], including pigs [21,22]. In certain instances, this strategy has resulted in improved accuracy of genomic prediction for growth and carcass traits in pigs, with improvements ranging from 0.9 to 46% for multi-breed populations [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al. (2023) found that, although some improvement in trait prediction accuracy was occasionally observed by increasing marker density, the increase in marker density did not translate into an increase in prediction accuracy in most cases, particularly for small population sizes.…”
Section: Discussionmentioning
confidence: 99%